MINAT SISWA TERHADAP PEMBELAJARAN SENI MUSIK DI SMP NEGERI 1 PAINAN KABUPATEN PESISIR SELATAN - Suyata Suyata; Tulus Handra Kadir; Marzam Marzam (SENDRATASIK UNP, 2013)
Abstract The purpose of this study was to reveal the picture of students' interest to wards learning the art of music in SMP Negeri 1 Painan South Coastal District. This type of researc his descriptive, while research conducted in February-March 2013. The instrument used was a questionnaire to collect data using a Likert scale. Data were analyzed using frequency distribution formula in the form of a percentage.  From the analysis of the data obtained the following results: 1. Minat siswa in SMPN egeri 1 Painan seen from the classification indicators are sufficient participation (74.1%).  2. Student interest in SMP Negeri 1 Painan seen from the classification indicators are sufficient attention to the percentage of75.7%. 3. Student interest in SMP Negeri 1 Painan seen from the feeling of being on the classification of the indicators enough with the percentage of 79.3%.  It means that of the three indicators of interest needs to be improved, so that students become better.   Kata kunci : Minat, pembelajaran, musik, deskriptif.